The Use of Mathematical Modeling in Shallow Seismic Data Processing for Detalization of the Heavy Oil Reservoir Structure - R.N. Sitdikov; A.V. Stepanov (Учёные записки Казанского университета: Серия Естественные науки)
Mathematical modeling plays an important role in understanding characteristics of the seismic wave field. In our opinion, it is one of the essential stages in any seismic survey. The paper sets out the methodology, which includes the steps of collection of geological data, creation and preparation of a seismic geological model, as well as some problems and new approaches to solving them for the upper part of the geological section of the Republic of Tatarstan. The process of building a 3D model of the structure of bitumen deposits using the ArcGIS software package and the modeling itself, which is performed using the Tesseral software package, are considered. The objects of study are the Ashalchinskoye deposit of the eponymous oil field and the Ulanovskoye deposit of the Novo-Chegodayskoe oil field. They are located on the western slope of the Southern dome of the Tatar arch. As a result, it is found that the bitumen deposit creates additional seismic events in the reflected field, as well as kinematic and dynamic anomalies. The results obtained allow to solve the problem of stratification of the reflecting horizons in the Upper Permian rock mass, which involves reservoir layers of the sand unit bearing heavy oil.